2012
DOI: 10.1089/lap.2012.0018
|View full text |Cite
|
Sign up to set email alerts
|

Early and Intermediate Outcomes of Laparoscopic Surgery for Choledochal Cysts with 400 Patients

Abstract: Laparoscopic repair is a safe and effective procedure for choledochal cyst. The rate of cholangitis and anastomotic stenosis is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 22 publications
3
76
1
13
Order By: Relevance
“…The attitude of those who approach for the first time to this type of minimally invasive approach should be to take a leaf from the vast experience of high volume centers in Asia (for instance Liem and Li). 4,5 Laparoscopic excision of CDCs has been supposed to give better observation, a better cosmetic result, potentially less postoperative pain, and a shorter recovery. 8 Jang and colleagues described a four port technique in 2006.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The attitude of those who approach for the first time to this type of minimally invasive approach should be to take a leaf from the vast experience of high volume centers in Asia (for instance Liem and Li). 4,5 Laparoscopic excision of CDCs has been supposed to give better observation, a better cosmetic result, potentially less postoperative pain, and a shorter recovery. 8 Jang and colleagues described a four port technique in 2006.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Laparoscopic cyst excision and hepaticojejunostomy for children with CDC have become feasible and popular recently. 3,4 Taking in consideration scarcity of cases in Italy, we present our early experience with three cases of type I CDC, which were operated by laparoscopic cyst excision and hepaticojejunostomy with extracorporeal Roux-en-Y anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence is much higher in Asian populations, and a female predominance of around 4:1 is consistently found in most series. [2][3][4] There is no obvious hereditary element in most CMs, though a recent review identified 10 pairs of familial occurrence (siblings and offspring) in the literature. [5] Conversely, six pairs of monozygotic twins have been described in which a distinct CM appeared in only one pair.…”
Section: Epidemiologymentioning
confidence: 99%
“…This alludes to the increased centralisation of expertise in those countries and the effect of high-volume surgery. [4] Minimally invasive resection is an advanced technique requiring considerable dexterity. Other techniques have been used to try to improve the quality of the biliary anastomosis -the Achilles heel of the entire operation.…”
Section: Fig 4 a And B Type 1c Cm: Ree-month-old Girl With A Cyst mentioning
confidence: 99%
“…1,2 Choledochal cyst related complications include cholecystitis, cholangitis, pancreatitis, cholelithiasis, and perforation of the choledochal cyst. Furthermore, choledochal cysts can transform into biliary malignancies if not treated.…”
Section: Introductionmentioning
confidence: 99%